The effects of propolis on serum malondialdehyde, fatty acids and some blood parameters in Japanese quail (Coturnix coturnix japonica) under high stocking density - Arslan, Aslihan Sur; Seven, Pinar Tatli (Taylor & Francis Ltd, 2017)
The objective of this study was to investigate the effects of dietary propolis supplementation of the basal diet on the fatty acids, serum malondialdehyde (MDA) and some blood parameters of Japanese quail feeding under high stocking density (HS). For that, 256 Japanese quail were divided into four treatment groups. Group I-HS fed on a basal diet, II-(HS-0.5) was fed on a basal diet supplemented with 0.5 g propolis/kg, III-(HS-1) was fed on a basal diet supplemented with 1 g propolis/kg, IV-(HS-1.5) was fed on a basal diet supplemented with 1.5 g/propolis/kg. MDA levels in serum (P < .01) were found to be significantly higher in the unsupplemented HS group. Globulin, total protein, lowdensity lipoprotein cholesterol (P < .001) and alanine aminotransferase (P < .01) levels of unsupplemented HS group were found to be significantly higher. Propolis supplementation significantly affected the lipid composition of internal organs (kidney and liver) of HS-0.5, HS-1 and HS-1.5 groups by decreasing saturated fatty acid contents and by increasing polyunsaturated fatty acid contents. Consequently, propolis supplementation improved the quality of lipid composition of the internal organs of quail. It might be considered to prevent the negative effects of stocking density.
Keywords: Quail; propolis; stocking density; malondialdehyde; fatty acids